Social Learning Theory in Clinical Setting: Connectivism, Constructivism, and Role Modeling Approach - Amir Khushk; Muhammad Ihsan Dacholfany; Dindin Abdurohim; Nasir Aman (Health Economics and Management Review)
The purpose of this study is to explore the social learning theory in terms of connectivism, constructivism, and role modeling approach in a clinical setting and its consequences. This article aims to analyze the possible role of connectivism, constructivism, and, role modeling as learning theories in terms of dealing with useful student learning instructional strategies. All these approaches are key concepts to align any level of education (primary, secondary, and particularly higher education). The research is qualitative in design and uses an inductive approach. Using a qualitative content analysis approach enables in-depth study of studies as well as data interpretation, leading to conclusions regarding the meaning of diverse experiences. The authors have given insight into designing teaching practices that adapt to changes in how management, physicians, and medical students observe, learn, communicate, generate and share new knowledge. The current study provides a summary of approaches and theoretical insights about planned and unplanned learning. This research will be valuable in developing role modeling instructional programs. Encouraging clinical instructors to make continual efforts to enhance role modeling and teaching time management and self-control skills can assist clinical teachers to overcome the problems of learning with role modeling. The finding shows that collective learning outperforms individualistic learning in terms of improving engagement, enhancing quality, and producing positive interpersonal outcomes. Encouraging clinical instructors to make continual efforts to enhance role modeling and teaching time management and self-control skills can assist clinical teachers to overcome the problems of role modeling. The building is a theory that affirms that learning is a process for the learner Role modeling is effective for medical students. The implications and future directions would be beneficial for researchers and academicians seeking to empirically extend their study on connectivism, constructivism, and role modeling approaches.